Insights into changing coastlines, environments and marine hunter-gatherer lifestyles on the Pacific coast of South America from the La Yerba II shell midden, Río Ica estuary, Peru. (1st June 2022) - Beresford-Jones, David G.; Friesem, David E.; Sturt, Fraser; Pullen, Alexander; Chauca, George; Moat, Justin; Gorriti, Manuel; Maita, Patricia K.; Joly, Delphine; Huaman, Oliver; Lane, Kevin J.; French, Charles
Abstract: Shell middens are conspicuous manifestations of the exploitation of rich, sustainable, easily seen and harvested marine resources that, worldwide, enabled hunter-gatherers to reduce mobility and increase population and social complexity. Globally, known sites tend to cluster chronologically around 6 k BP, after slowing eustatic sea-level rise, although the Pacific coast of South America offers some rare earlier exceptions. We report investigations of La Yerba II, a Middle Preceramic shell matrix site on the Río Ica estuary, south coast Peru. These show how, beginning around 7000 Cal BP, over 4.5 m of stratigraphy accumulated in less than 500 years. Consisting of prepared surfaces, indurated floors and the ashy interiors of wind shelters and their associated midden deposits, alternating with phases of abandonment, this was the outcome of an intense rhythm of repeated occupations by logistically mobile marine hunter-gatherers. Final phases, dominated by Mesodesma surf clams, mark change towards more task-specific activities. La Yerba II's topographic position and well-preserved cultural and environmental markers provide insight into the local history of relative sea level change and changing marine hunter-gatherer lifestyles during a period critical to the transition to sedentism and the formation of new estuarine and beach habitats following the stabilisation of eustatic sea-levels. Highlights: We investigate La Yerba II a large shell midden on the Río Ica estuary, south coast Peru. We show how, beginning around 7000 BP, over 4.5 m of midden stratigraphy accumulated in less than 500 years. These consist of prepared floors, ashy wind shelter interiors and middens, alternating with phases of abandonment. They are the outcome of an intense rhythm of repeated occupations by logistically mobile marine hunter-gatherers. La Yerba II's position today also documents relative sea level change through on-going tectonic uplift along this coast.